MEMBACA DAN MENULIS AL-QURAN DAN HADITS, DAN KAITANNYA TERHADAP KEIMANAN/AQIDAH STRATEGI PEMBELAJARANNYA - Ramadhan, Nurmansyah; Irwansyah, Arief; Irawan, Ayu; Ervina, Ervina (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
Reading and writing the Qur'an and Hadith are fundamental skills that every Muslim must master, particularly for gaining a profound understanding of Islamic teachings. The Qur'an and Hadith serve as the primary guides in forming a robust aqidah (creed), which is the cornerstone of a Muslim's faith. This research employs a qualitative approach through a literature study. The data in this article are derived from various literary sources, including books, scientific articles, and other academic references that support the investigation into reading and writing the Qur'an and Hadits, faith/aqidah, and their respective learning strategies. The ability to comprehend the Qur'an and Hadith equips students with a strong foundation of faith and correct aqidah, enabling them to navigate life's challenges with firm conviction while adhering to Islamic principles